Investigating hydrate formation and flow properties in water-oil flow systems in the presence of wax - Liu, Yang; Meng, Jiawei; Lv, Xiaofang; Ma, Qianli; Shi, Bohui; Wang, Chuanshuo; Huang, Huirong; Wu, Chengxuan; Zhou, Shidong; Song, Shangfei (Frontiers in Energy Research, 2022)
The coexistence of wax and hydrates will pose intractable challenges to the safety of offshore oil and gas production and transportation, especially for deep sea or ultra-deep sea reservoirs. Understanding the effect of wax crystals on hydrate formation, flow properties and plugging risks of flow systems is imperative to flow assurance industry. Experiments using systems composed of natural gas, water-in-oil emulsion with different wax contents and AA (anti-agglomerant) were conducted in a high-pressure flow loop. For wax-containing systems, wax precipitated out during the induction period of hydrate formation. The induction time of hydrate formation decreased with the increasing wax content under the experimental condition in this work. It was also found that the induction time for both wax-free and wax-containing systems increased with the increasing flow rate. The hydrate growth rate and the cumulative gas consumption significantly reduced due to the existence of wax. Although the hydrate volume fraction of wax-containing systems was much smaller than that of wax-free systems, a stable slurry flow state could not be reached for wax-containing systems, the pressure drop of which gradually increased with the decreasing flow rates. The coexistence of wax and hydrates resulted in the deterioration of transportability and higher plugging risks. Based on the Darcy-Weisbach hydraulic formula, a dimensionless parameter was defined to characterize the plugging risk of flow systems with the coexistence of wax and hydrates. Additionally, regions with different level of plugging risks could be evaluated and divided.